Downshifting and upconversion dual mode emission from lanthanide doped GdPO4 nanorods for unclonable anti-counterfeiting. (March 2021) - Pushpendra; Suryawanshi, Indranil; Srinidhi, Saumya; Singh, Sarabjot; Kalia, Rimple; Kunchala, Ravi K.; Mudavath, Shyam Lal; Naidu, Boddu S.
Graphical abstract: Abstract: Due to increasing counterfeiting day by day, it is important to protect valuable documents such as certificates, diplomas, currency, bank-notes and luxury brands from counterfeiters. Herein, we report the synthesis of downshifting and upconversion dual mode emitting GdPO4 nanorods by a simple co-precipitation method. The crystal structure of GdPO4 has been tuned from hexagonal to monoclinic by controlling the reaction temperature from 100 to 185 °C. Both hexagonal and monoclinic GdPO4 nanomaterials exhibit rod-shaped morphology. Europium doped GdPO4 nanorods show excellent photoluminescence properties and strong orange-red luminescence under UV light. The quantum efficiency is improved from 31 % to 52 % as phase transform from hexagonal to monoclinic. Erbium, ytterbium co-doped nanorods shows strong upconversion emission in the visible region. Europium, erbium and ytterbium tri-doped nanorods shows both downshifting and upconversion emission in the visible region upon excitation with UV, NIR light. Further, luminescent security ink is made from monoclinic GdPO4 nanorods to print different kinds of security patterns and these white security patterns turns into bright orange-red color patterns under UV and NIR light. Therefore, the luminescent security ink can be used for anti-counterfeiting applications to combat counterfeiting.